2015
DOI: 10.1080/19336896.2015.1022022
|View full text |Cite
|
Sign up to set email alerts
|

The ribosome-associated complex antagonizes prion formation in yeast

Abstract: ABSTRACT. The number of known fungal proteins capable of switching between alternative stable conformations is steadily increasing, suggesting that a prion-like mechanism may be broadly utilized as a means to propagate altered cellular states. To gain insight into the mechanisms by which cells regulate prion formation and toxicity we examined the role of the yeast ribosome-associated complex (RAC) in modulating both the formation of the [PSI C ] prion -an alternative conformer of Sup35 protein -and the toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 77 publications
2
35
0
Order By: Relevance
“…However, we have demonstrated that Ssb deletion is toxic in the presence of Sup35 overexpression, indicating that chaperone function is necessary. Further, perturbations that prevent Ssb association with the ribosome have been shown to enhance yeast sensitivity to Sup35 overexpression [36]. We suggest that the toxicity rescue observed in the NAC deletion strains is due to a shift in Ssb activity to nascent proteins.…”
Section: Discussionmentioning
confidence: 76%
“…However, we have demonstrated that Ssb deletion is toxic in the presence of Sup35 overexpression, indicating that chaperone function is necessary. Further, perturbations that prevent Ssb association with the ribosome have been shown to enhance yeast sensitivity to Sup35 overexpression [36]. We suggest that the toxicity rescue observed in the NAC deletion strains is due to a shift in Ssb activity to nascent proteins.…”
Section: Discussionmentioning
confidence: 76%
“…Plates were incubated at 30°C for 3 days (without ZnCl 2 ) or 4 days (with ZnCl 2 ) and then photographed. Colony area (pixels^2) for 161-326 isolated, single colonies was measured as previously described [48] [49].…”
Section: Yeast Growth Assaysmentioning
confidence: 99%
“…Cells to be transformed were first grown sequentially (three times) on agar medium supplemented with 5 mM guanidine hydrochloride (ACROS Organics) to eliminate [PSI + ] and [RNQ + ] prions (elimination of [RNQ + ] by this treatment in these strains has been previously confirmed by lack of visible GFP foci in cells over-expressing Rnq1-GFP [48]; and our unpublished data). Cells were then treated with 100U of lyticase (Sigma) in 1 M sorbitol + 10 mM Tris pH 7.5 at 30°C for 1 hour to generate spheroplasts.…”
Section: Protein Transformation With [Psi + ] Si-str and [Psi + ] Sc3mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, however, different defects of the ribosome associated chaperone complex (RAC) induced in zuo1, ssz1 and ssb1 ssb2 mutants all increased de novo generation of the [PSI C ] prion. [24][25][26] This may suggest that interference with translation at the level of tRNA functionality might impact on the tendency to form spontaneous amyloid aggregates as well, since similarities in protein homeostasis defects with the RAC mutants exist. However, dual tRNA modification loss affecting tRNA …”
Section: Future Directionsmentioning
confidence: 99%